One last chance - Martin, Kat (Kensington Publishing Corp., 2022)
When former Green Beret Edge Logan offers to help fellow agent Skye Delaney with a case involving her missing sister and a mysterious cult, they infiltrate the cult's compound, working against the clock to unmask the face of evil--and their feelings for each other--before time runs out.